The Effectiveness of Media Zoom Meetings as Online Learning during the Covid-19 Pandemic. - Nana Erna; Risma Asriani Azis Genisa; Fadel Muslaini; Titin Suhartini (ELT-Lectura, 2022)
This research is descriptive. The purpose of this study was to determine the effectiveness of the Zoom meeting media as a distance learning medium during the covid-19 pandemic to suppress the spread of the virus. This research was carried out at Sawerigading University Makassar, especially for English education department students who are active in the writing I course. The research instruments used were test instruments and questionnaires. The instrument test was carried out to determine student learning outcomes in the form of an essay test of 20 questions with a completion time of 90 minutes while the positive response questionnaire aimed to see student responses to the effectiveness of the Zoom meeting media as a learning medium. The results of student learning outcome using zoom are complete as much as 86% the results obtained were 26 students scored 70-95 and 4 students scored below 70. While the results of the positive response questionnaire students met the effectiveness criteria with above 80% so that it can be categorized as learning media using zoom during the covid-19 pandemic for writing I course is effective. Keywords: Effectiveness, Zoom Meeting, Writing I